Assessing Hydrocyclone System’s Efficiency in Water-Borne Microplastics Capture Using Online Microscopy Sensors - Pajuro, Kacper; Yang, Zhenyu; Jespersen, Stefan; Hansen, Dennis Severin (Sensors (Basel, Switzerland), 2025)
Plastic pollution has been a global concern. Microplastics are often referred to as plastic particulates whose sizes are within the range of 1 μm to 5 mm. To cost-effectively capture these tiny microplastics from open environments, such as from the air or aquatic/marine systems, is far from trivial. Not only is some innovative capturing technology demanded, but some online monitoring solutions are often requested as well to assess the capturing effectiveness and efficiency, as well as provide some feedback information to the control system to adapt to varying operating conditions. Inspired by the de-oiling treatment of the produced water in offshore oil & gas production, this paper explores the potential to apply the hydrocyclone technology to cost-effectively handle the water-borne microplastics, and its effectiveness is demonstrated based on reliably calibrated online microscopy measurements subject to artificial polyethylene particulates added to the water stream. The experimental work is carried out using a commercial de-oiling hydrocyclone system and a set of commercial optical microscopy sensors. A statistic-based calibration method is firstly proposed for the deployed microscopy sensors to select the best calibration parameters. Afterwards these sensors are installed at the inlet and water-outlet of the hydrocyclone system via a side-stream sampling mechanism to assess this system’s (microplastics) separation efficiency subject to dynamical operating conditions, which are mimicked by manipulating its underflow and overflow control valves via PI-controlled loops. The separation efficiencies are calculated based on these volume concentration measurements and compared between the case with (statistically) optimal calibration parameters and the case with a set of non-optimal parameters. The best separation efficiency of 87.76% under the optimal calibration parameters is observed under a specific operating condition. The obtained result shows a promising potential to use these separation and sensing systems to cost-effectively handle aquatic microplastics collection, though it also indicates that a further higher efficiency could be achieved by some (microplastics) dedicated cyclone design combined with a dedicated process control system, and this is one part of our ongoing research work.